Standardization of Basic Movement “Belanjakan” of Martial Arts on East Lombok Regency - Hidayatullah, Muhammad Riyan; Rahayu, Tandiyo; Wahyudi, Agung (Journal of Physical Education and Sports, 2019)
Standardization of basic movements of “Belanjakan” martial is intended to explore, develop, and preserve martial arts that grow and develop as a culture of Masbagik people of East Lombok Regency. The purpose of the study is to examine and analyze the basic movements of stance, footstep patterns, defense, and attacks